Solid pseudopapillary epithelial neoplasm of pancreas presenting as an abdominal lump: a case report - Gupta, Niraj; Kumar, Rohit; Verma, Amar; Nabh, Rishi; Sharma, Vivek; Rathaur, Arun (International Surgery Journal, 2023)
Solid pseudopapillary epithelial neoplasm (SPEN) of the pancreas is a rare cystic exocrine tumour of the pancreas that predominantly affects women between 30 and 40 years of age. This case report aims to describe clinical presentation and management of SPEN. We report a case of 20 years old female who presented with palpable lump in upper abdomen and continuous dull aching pain. Preoperative contrast enhanced computed tomography (CECT) abdomen was suggestive of large solid mass of size 11×10×10 cm with liquified content in relation to tail of pancreas with a possibility of retroperitoneal tumour or gastrointestinal tumour (GIST). Spleen sparing distal pancreatectomy with segmental resection of transverse colon with colo-colic anastomosis was performed and the diagnosis of SPEN was subsequently confirmed on histopathology examination. SPEN is a slow-growing tumour with a low-grade malignant potential found incidentally in asymptomatic patients. The average tumour size is about 4 to 6 cm in diameter at presentation. Distal pancreatectomy with splenectomy is the procedure of choice as described in literature. SPEN should be kept as a differential diagnosis in a young female patient presenting with vague abdominal pain and retroperitoneal lump in relation to the pancreas. Complete surgical resection is the definite treatment with a 5-year survival rate of 95%.